Poverty and the realization of the millennium development goals in Nigeria: disability rights the missing link (2011)
The Millennium Development Goals (MDGs) being the world’s time-bound and quantifiable targets for addressing extreme poverty in its many dimensions, do not specify actions for addressing poverty in the lives of disabled people. This article examines the cyclic nature of the relationship between disability and poverty and argues that discrimination against disabled people occasions poverty and unless the relationship between disability and poverty are put in proper perspective that mainstreams disability, the MDGs will not be realized in Nigeria. It suggests deliberate efforts at combating poverty and human right denials in the implementation of the MDGs in view of the serious challenge that poverty poses to people with disabilities in developing countries. It examines disability, discrimination and poverty and how they relate, and then concludes that though not mentioned in the MDGs, disability must be mainstreamed in the process of its implementation.